Exploring the Effects of Threat-Based Climate Change Content in Canadian Post-Secondary Environmental Education - Collette, Emma (University of Waterloo, 2024)
When college students are asked how they feel about climate change, instead of motivation or empowerment, the most common response is fear (Hiser & Lynch, 2021; Galway & Field, 2023). Although this is deeply concerning, it comes as no surprise when you consider the material they are exposed to. Climate change is a growing threat to human life (Santamouris, 2020; Shindell et al., 2020; Silva et al., 2017; Lloyd et al., 2016), and this reality is reflected in the news, on social media, and in the classroom (e.g., CBC, 2023; Canada’s NDP, 2023; Canadian Climate Institute, 2022; Vieyra-Balboa et al., 2024). As of now, researchers don’t know exactly how this threat-based content is affecting students in environmental education programs. However, there is strong evidence that this type of messaging can affect peoples’ behaviours (Burke et al., 2010), including their environmental behaviour (Fritsche & Hafner, 2012; Fritsche et al. 2012). The purpose of my study was to examine the ways that threat-based climate change content affects post-secondary students in environmental studies programs. Two of my primary research objectives were to compare outcomes in 1) students’ environmental identities and 2) students’ actual short-term pro-environmental behaviour. My third objective was to produce findings that could be used to inform approaches to climate change education and contribute to the growing literature on climate change and mortality threats. I did this by presenting student participants with one of three randomly assigned news articles on an online survey platform: a Threat-Based climate change article, an Informational climate change article, or a Control article unrelated to climate change. After students had read their article, I measured their environmental identity and short-term pro-environmental behaviour so that I could compare the outcomes of students from the three conditions. I found that the news articles did not have a significant effect on identity, but that there was a decrease in pro-environmental behaviour for students who read the climate change articles (significant effect for the Informational and marginally significant for the Threat-Based). My study produced several academic contributions, including the application of valuable methodological approaches, as well as guidance for future climate change education research. Based on my findings, I would not recommend Threat-based climate change content as a productive avenue for inspiring pro-environmental behaviour in post-secondary environmental education students. However, I recognize the importance of dispelling the reality of the climate crisis, including the threatening components, and make several recommendations for ways to mitigate the risk of behavioural inhibition when presenting this content. These findings can be used to inform educational climate change content so that educators can be empowered to select approaches that foster wellness and action.
Keywords: climate change; environmental education; terror management theory; pro-environmental behaviour